2000
DOI: 10.1002/(sici)1096-9888(200004)35:4<572::aid-jms971>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an artifact in the mass spectrometry of proteins derivatized with iodoacetamide

Abstract: Derivatization of cysteinyl residues is often used to prevent the formation of disulfide bonds during protein isolation and analysis. The most commonly used reagents are iodoacetic acid and iodoacetamide, which increase the molecular mass of the protein by 58 or 57 Da, respectively, for each derivatized cysteine. A possible side reaction is derivatization of methionine. In our analysis of derivatized human lens αA‐crystallins, we found an apparent molecular mass 48 Da lower than the mass expected for αA‐crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 6 publications
4
42
0
1
Order By: Relevance
“…The mass of 1852 is contributed from the peptide with methionine oxidized to methionine sulfoxide (with a mass increase of 16 Da) (5) and the asparagine from the consensus sequence modified to aspartic acid (with a mass increase of 1 Da) after PNGase F deglycosylation (28). The mass of 1791 is attributed from the same peptide as shown by the CID spectrum with a cleavage between the ␥ carbon and the sulfur of the methionine side chain, which most likely happened during the mass spectrometry direction (33)(34)(35). The successful identification of the formally glycosylated peptide from chicken avidin indicated that the capture strategy we developed here was effective and that the sodium sulfite we introduced to reduce periodate did not interfere with the capture procedure.…”
Section: Resultsmentioning
confidence: 99%
“…The mass of 1852 is contributed from the peptide with methionine oxidized to methionine sulfoxide (with a mass increase of 16 Da) (5) and the asparagine from the consensus sequence modified to aspartic acid (with a mass increase of 1 Da) after PNGase F deglycosylation (28). The mass of 1791 is attributed from the same peptide as shown by the CID spectrum with a cleavage between the ␥ carbon and the sulfur of the methionine side chain, which most likely happened during the mass spectrometry direction (33)(34)(35). The successful identification of the formally glycosylated peptide from chicken avidin indicated that the capture strategy we developed here was effective and that the sodium sulfite we introduced to reduce periodate did not interfere with the capture procedure.…”
Section: Resultsmentioning
confidence: 99%
“…Sequence of phosphoribosylformylglycinamidine cycloligase (SO_2760) in Shewanella oneidensis MR-1 according to TIGR annotation (red), observed nontryptic peptide (blue) and alignment to the orthologs in other Shewanella strains (green). Lagerwerf et al 1996;Lapko et al 2000 Carbamidomethylation (abbreviated as CAM) is added to cysteine side chains by treatment with iodoacetamide, but can be attached to other sites. Most of these modifications occur in vitro.…”
Section: Chemical Modificationsmentioning
confidence: 99%
“…With a pKa of about 8.3 for protein thiols, it is clear that the Cys thiol will be most reactive at high pH. Side reactions that may occur include alkylation of His, Lys, Met, or Tyr residues by the iodoacetamide [18]. In contrast, maleimides proceed via Michael addition where the nucleophile (thiolate) reacts with the olefin (maleimide).…”
Section: Optimization Of Labeling With Bodipy Fl-mal In the Presence mentioning
confidence: 99%